Study guides

☆☆

Q: What is 2a plus 2b in factored form?

Write your answer...

Submit

Still have questions?

Related questions

(a - 2b)(2a - b)

2a + 2b = 4

4(2b+5)

you find the GCF divide by GCF to get awnser like 2a+2b GCF 2 dived by to to get a+b

a-b+a-b+2b+a = 4a

1

It is 2a-b simplified

2a + 2b = c subtract 2a from both sides 2a - 2a + 2b = c - 2a 2b = c - 2a divide both sides by 2 (2/2)b = (c - 2a)/2 b = (c - 2a)/2 --------------------

-2a plus 3b

6a2 + 5ab - 6b2 = 6a2 + 9ab - 4ab - 6b2 = 3a(2a + 3b) - 2b(2a + 3b) = (2a + 3b)*(3a - 2b)

a-^2a-b^-a-b

It is: 2a(2b+c)

= a + b - 2

ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.

3+2*A+B*4/2-4 = 3 + 2A + 2B - 4 = 2A + 2B - 1

(x + 2)(a + b)

Do this: write it out 2 |2a + 4b + 8 Now what divides into all the numbers? ---------------- a + 2b + 4 answer is 2(a+2b+4)

6 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -3

It is: 3a(2b -3c) when factored

2a

2a+2b+3a+3b+a+b= 6a+6b 2a+3a+a=6a 2b+3b+b=6b

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)

Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).

a + 7b + 2c

2a + 2b = 160 But b = a + 40 so 2a + 2(a + 40) = 160 ie 2a + 2a + 80 = 160 or 4a = 80 ie a = 20 Then b = a + 40 gives b = 20 + 40 = 60 Solution: a = 20, b = 60